PATIENTS SATISFACTION ANALYSIS OF PRIMARY HEALTHCARE SERVICE QUALITY IN BONDOWOSO, INDONESIA - Nazhifah, Naurah; Bachtiar, Adang; Oktamianti, Puput; Candi, Cicilya (Universitas Pahlawan Tuanku Tambusai, 2023)
Indicators of efficiency and quality in healthcare often include patient satisfaction with the care they received. Health managers and policymakers may benefit greatly from the information gleaned from patient satisfaction surveys when conducting analyses of the existing state, awareness, quality, and quantity of process improvement initiatives and quality improvement. Improving patient satisfaction and providing patient-centered care relies heavily on meeting and even exceeding patients' expectations of the health care they get. There is still limited data about patients’ satisfaction and service quality in Bondowoso’s Primary Health Care. Therefore, this study was made to measure patients' satisfaction toward service quality in Bondowoso‘s Primary Healthcare. This is quantitative cross-sectional primary research. The data was collected using a questionnaire with 22 pairs of questions (organized in two aspects of service importance and performance) in 5 dimensions of tangibility, reliability, responsiveness, assurance and empathy. The importance-performance analysis (IPA) was used to determine the weaknesses of service quality and prioritizing the aspects requiring improvement. Data was collected at Primary Health Care Raider 514 Bondowoso from February to March 2023. Samples were filtered with several inclusion criteria based by age, residence, and their status as a patients in Primary Health Care Raider 514 Bondowoso. From 72 respondents, 54.2% (n=39) was Male, 81.9% (n=59) age were under 46 years old, 37.5% (n=27) had university degree, and 65.3% (n=47) were employed. The result of IPA showed that the Assurance in the QI (concentrate here), and reliability and responsiveness in the Q II (keep up the good work). tangible in the Q III (low priority), empathy was located in the Q IV (possible overkill). According to our findings, assurance was an aspect which was prioritized for improvement. A more comprehensive operational standard could improve assurance. Results are limited only to 1 primary health care site from February to March 2023 and limited to first level health facility patients only.